The European Network on Psychosomatic Medicine (ENPM) – history and future directions - Deter, Hans-Christian (Biopsychosoc Med, 2017)
BACKGROUND: Within national and international societies of psychosomatic medicine the idea has emerged of bringing together and coordinating psychosomatic, behavioural, psychological and medical actions with common interests throughout Europe as a way to increase their scientific and political influence. METHODS: It was felt that there was a strong need and opportunity of a common and unifying forum for scientific exchange. RESULTS: It was considered desirable to exchange scientific thoughts and experiences in an open minded and boundless way, among individuals and societies, between disciplines and across borders. The course of ideas and discussions within the group of European psychosomatic scientists over 12 years is presented as an effort to combine strengths and actions supporting clinical psychosomatic research and medical practice in Europe. The fields of psycho-cardiology, quality in primary care, psycho-oncology, gastrointestinal psychosomatics, C/L Psychiatry, and Psychosomatics are examples of such positive developments. DISCUSSION: Several historic ideas are mentioned and the aims and advantages of the newly founded European Association of Psychosomatic Medicine are discussed. The advantages and virtues of a more powerful common European organisation of Psychosomatic Medicine and Psychiatric Consultation-Liaison are compared to continuing our work within the present Psychosomatic/Psychiatric and Behavioural fields. CONCLUSION: Psychosomatic and Behavioural Medicine have reached a strong position in Europe. There are studies in which the medical speciality is on equal terms with psychosomatic medicine representatives. There is a continuous need for scientific conferences, for teaching, and for better practice with patients. This could be coordinated by a network. Much energy and time is lost in isolated societies and countries. We want to focus our resources in scientific projects within the boundaries of a scientific network with the primary aim of developing psychosomatic scientific exchange.